Efektifitas Buku Suplemen Pencegah COVID-19 Berbasis Digital untuk Memberdayakan Keterampilan Ilmiah dan Literasi Keterampilan Berpikir Kritis Siswa SMA - Fitri Arsih; Ravy Ferdian; Muhyiatul Fadilah (Jurnal Penelitian Pendidikan IPA, 2023)
The development of teaching materials such as digital-based supplementary books really needs to be done considering that COVID-19 has not yet been integrated with biology subjects. Students need to dig up information about COVID-19 through scientific literacy and solve problems through critical thinking. This study aims to determine the effectiveness of digital-based supplement books through quasi-experiments by looking at the comparison of pre-test and post-test results. The data were analyzed quantitatively to determine the category of effectiveness and deepened by a qualitative analysis of the influencing factors. Sig. The value of (2-tailed) Paired T-test is 0.000. which shows that there is a difference in the average learning outcomes before and after using the supplement book. This means that the COVID-19 prevention supplement books greatly affect students' scientific literacy skills and critical thinking skills. Scientific literacy is enhanced because the content in the book explores COVID-19 information and is integrated into the material. Meanwhile, critical thinking is empowered with direction analysis and decision making in books. The book developed is predicted to be very useful and supportive in learning biology, especially relevant material such as material about viruses, the respiratory system, and the immune system